Upaya Meningkatkan Hasil Belajar Ekonomi Dengan Menggunakan Model Kooperatif Tipe Investigasi Kelompok Pada Peserta Didik - Eny Puspitasari; Supardi Supardi (Neraca: Jurnal Pendidikan Ekonomi, 2017)
This study aims to determine the increase in economic learning outcomes and activities of students of class XI IPS 1 in Palangka Raya Muhammadiyah High School in economic learning using cooperative learning models of group investigations. The method used in this study was to use the Classroom Action Research design. The subjects in this study were 23 students. The results of the study showed that the learning outcomes and learning activities of students increased. This is evident from the average score of economic learning activities of students in the first cycle to the second cycle, which is 43.8 which includes a category increased to 47 which includes a very increasing category. the pre-test learning outcomes averaged 52.82 with 39% completeness, the post-test results in the first cycle average score 77.39 with completeness 69.5%, and the post-test results in cycle II averaged 99.13 with completeness 100% criteria are very achievable.